The Model of GDP Growth in ASEAN-4 Countries: Control of Corruption as an Intervening Variable - Benny Budiawan Tjandrasa; Vera Intanie Dewi (Journal of Economics, Business, and Accountancy Ventura, 2022)
The purpose of this study is to analyze various macroeconomic factors that affect Gross Domestic Product growth in ASEAN-4 countries. The type of research is descriptive and explanatory. The research method used is the quantitative method. Based on the phenomenon, purposive sampling is used to determine the countries studied. Using secondary data, the panel data is formed from a combination of countries and a certain period of years. Multivariable regression is used to process panel data. The results show that inflation rate, political stability, and control of corruption have a significant effect on GDP growth. The novelty of this research is the new model of GDP growth in ASEAN-4 countries where control of corruption serves as an intervening variable that affects GDP growth. The findings suggest that to maintain an increase in GDP growth in this region, the governments should keep the inflation rate under control and continue striving to reduce corruption. Controlling the level of corruption can be done by maintaining the stability of the political situation and controlling the inflation rate.